The French book illustration in the Russian cover-version at the end of XVIII century - Borshch, Elena (Przegląd Wschodnioeuropejski, 2018)
The focus of this article is the illustrations from the Russian edition of Ovid’s Metamorphoses of 1794–1795, which have been repeated from the unknown foreign book. The result of this research is a finding of the source of the Russian illustrations, the engravings from the Dutch edition of 1732 intended for the French book market. There is an attempt to prove authorship of these anonymous illustrations in the article, which includes comparisons of illustrations from the Dutch, Flemish, French and Russian editions. Thus the Russian illustrations were neither copies, nor free variations on a theme. They have appeared as mirror versions and replicas with the changed details of the illustrations of 1732.